Reading Comprehension and Literary Appreciation: an Analysis of Students Difficulties - Erniwati, Erniwati; Mertosono, Sudarkam R; Maghfira, Maghfira (Universitas Negeri Makassar, 2023)
Abstract. This research aims to analyze difficulties encountered by students of the English Education study program at Tadulako University in reading comprehension of literary works. A qualitative approach with a descriptive research design applied in this research. The samples were 98 students chosen randomly. Data were collected from existing documents, that is the results of pretest administered in the Reading for Literary Appreciation class. Results of data analysis showed that the students’ reading comprehension of the three genres of literary works – prose, poetry, and drama is low with percentage intervals of comprehension 18-37%. Eight difficulties encountered by the students in reading comprehension of literary works. They were vocabulary mastery, making inferences, recognizing the author’s opinion/bias, summarizing and paraphrasing, identifying figurative language, analyzing poetic or sound devices, evaluating author’s style, and analyzing the story elements. The findings provide information on students’ difficulties in reading comprehension of a variety of literary texts (prose, poetry and drama), which previous research have not yet investigated it. Therefore, teachers can design and apply strategies to help students improve their reading comprehension. Future researchers, furthermore, can find these findings resourceful to support their studies. Keywords: Reading Comprehension, Literary Works, Reading for Literary Appreciation